Use of Foreign Experiences and World Pedagogy in Elementary Education Teaching - Qumrinisa Saidaliyevna Usmonova (Academia One Publishing, 2023)
The article presents the advantages of using global pedagogy in primary education and how to use it, as well as the use of foreign experiences in education.
Keywords: pedagogy of world nations; foreign experiences; Buyuk didaktika